COMPARISON OF GLOMERULAR FILTRATION RATE IN DIABETIC NEPHROPATHY PATIENT WITH COMORBID HYPERTENSION AND MEDICATION ADHERENCE - Jimmy Chua; Yohanes Firmansyah; Joshua Kurniawan; Ernawati Ernawati (Jurnal Medika Hutama, 2021)
Background: Chronic Kidney Disease (CKD) is a global health problem with increasing prevalence and incidence of kidney failure, bad prognosis, and high treatment cost. The prevalence of CKD increases with the increasing number of elderly population and the incidence of diabetes mellitus and hypertension. Comorbidities of patient with CKD, according to Indonesian Renal Registry in 2018, are hypertension or uncontrolled blood pressure (51%) and type 2 diabetes mellitus (21%). Methods: Cross-sectional studies of patients in “RT” Hospital Jakarta between 2018-2019. The independent variable in this research is hypertension comorbidities and medication adherence, whereas glomerulus filtration rate as the dependent variable. the correlation of cause and effect is tested with Independent T-Test and Mann Whitney Test as an alternative. Findings: The research includes 26 respondents, with prevalence of hypertension in diabetic nephropathy patient of 17 (65,4%). Population of patient with diabetic nephropathy with hypertension comorbidities has lower glomerular filtration rate (GFR) compared with group of diabetic nephropathy patients without comorbid hypertension (14.4% vs 28.6%). Hypertensive patients with no routine treatment have average GFR of 8.5%, and hypertensive patients with routine treatment have GFR of 16.15%. Statistical test results with Mann Whitney shows that there are no meaningful difference in average GFR between the two groups (p-value: 0.130).Conclusion: Blood pressure control and medication adherence can slow down the decline in renal function caused by complication of diabetic nephropathy, although there are no meaningful relation found in this research because of lacking in samples.